A Balanced Atmospheric Ensemble Forcing for Sea Ice Modeling in Southern Ocean. Issue 5 (27th February 2023) - Luo, Hao; Yang, Qinghua; Mazloff, Matthew; Chen, Dake
Abstract: To deal with the great challenges in simulating the highly non‐linear physics of Antarctic sea ice, a multivariate balanced atmospheric ensemble forcing is developed based on the high‐resolution component of ERA5, which considers the relationship between different variables and adjacent times. To validate the performance of this new forcing, experiments were conducted from 1 January 2016 to 28 February 2017. Compared to simulations forced with the ensemble component of ERA5, a more reasonable ensemble of simulations is produced by the atmospheric ensemble forcing developed in this study, which suppresses the sea‐ice concentration (SIC) simulation errors and produces a better estimation of SIC simulation uncertainties. Further sea‐ice thickness budget analysis reveals that this impact of atmospheric ensemble forcing on sea ice simulation is due to a modulation of atmosphere‐ocean and sea ice‐ocean thermodynamic processes. These results lay the foundation for further improvements in Antarctic sea ice data assimilation and probabilistic prediction. Plain Language Summary: Antarctic sea ice plays an important role in the Earth system. However, its accurate simulation still faces many challenges. Considering the highly non‐linear sea ice processes, adopting an ensemble simulation procedure is a way to improve Antarctic sea ice modeling skill. Perturbing the sea ice‐ocean coupled model indirectly through the atmospheric ensemble forcing can ensure the dynamic consistency of model states. In this study, we developed a method to perturb high‐frequency ERA5 reanalysis in a multivariate balanced way for the Southern Ocean coupled sea ice‐ocean model. Results show obvious improvements in the Antarctic sea ice simulation with the newly developed atmospheric ensemble forcing from both deterministic and probabilistic perspectives, which is achieved by modulation of atmosphere‐ocean and sea ice‐ocean thermodynamic processes. This is an important step toward the development of a comprehensive reanalysis for the sparsely observed Antarctic sea ice, which should benefit the scientific research and human activities in the Southern Ocean. Key Points: A multivariate balanced atmospheric ensemble forcing is developed for the Southern Ocean coupled sea ice‐ocean model Adopting this new forcing can suppress model errors of sea‐ice concentration and produce better estimates of simulation uncertainties The improvement is primarily caused by atmosphere‐ocean and sea ice‐ocean thermodynamic processes